The Influence of Green Product Attributes, Consumer Characteristics, and Environmental Awareness on Sosoft Detergent Purchase Intention - Natasya Citra Pramesti; Audita Nuvriasari (LifeSciFi, 2025)
Increasing environmental concerns have driven demand for eco-friendly products, particularly among young consumers in urban areas like Yogyakarta. This study aims to analyze the influence of green product attributes, personal factors, and environmental awareness on the purchase intention of Sosoft eco-friendly detergent. The research employs a quantitative approach, collecting data through questionnaires from 100 respondents aged 17 to 31 years, selected using purposive sampling to target individuals familiar with Sosoft and active on social media platforms. Data analysis includes descriptive statistics, multiple linear regression, and diagnostic tests for validity, reliability, normality, multicollinearity, and heteroscedasticity. Findings reveal that green product attributes and environmental awareness significantly influence purchase intention, explaining 34.1% of its variance, while personal factors, such as income and lifestyle, show no significant effect, likely due to economic constraints among young consumers. The results highlight the importance of promoting eco-friendly features and environmental awareness through social media to boost Sosoft’s appeal. Future research should explore additional factors like price sensitivity and expand the sample beyond Yogyakarta to enhance understanding of green product adoption.